Is marketing missing in the Liga F? Generation Z perceptions towards the Spanish professional women's soccer league - Flores, María Sierra; Barberá, Rafael; García, César (Transformations In Business & Economics, 2026)
Women’s soccer in Spain has captured global attention, propelled by Spain's victory in the World Cup (2023) and the global scandal involving the President of the Federation. Nonetheless, this competition remains modest in terms of revenue. Although support for and concern about feminism vary among Generation Z, they remain notably strong in Spain (Hernández-Arriaza et al., 2023, p.1; Vilanova, 2019, p.43) and beyond (Twenge, 2023). This article examines Generation Z's perception of the Spanish women’s soccer league to assess their interest and verify whether it is driven by the hypotheses in the theoretical framework of feminism and gender equality or by the appeal of sportainment and communication. To achieve this, a quantitative survey was conducted with 203 students to carry out an exploratory analysis and hypothesis testing. The results confirm the influence of sportainment and communication (p < 0.05), but do not provide statistical support for the gender equality hypothesis (p > 0.05). The study concludes that while members of Gen Z acknowledge and support gender equality, their interest in following a competition such as Liga F would require a major dose of sportainment through gamification, free access, which is the opposite of what Liga F offers.
Keywords: sportainment; sport marketing; soccer; Liga F; Generation Z; women